Companion Strategy for Acceptance of HIV/AIDS Status in Women - Lolita Sary; Syaripudin Basyar; Shonhaji Shonhaji; Fitri Yanti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: Women infected with HIV/AIDS had a double burden, including health, economic, mental, and social problems, and access to health services. Self-acceptance of HIV/AIDS status has always been a problem when women are diagnosed with HIV/AIDS, and companions are often needed to solve it. This study aimed to know the success of self-acceptance and companion strategies for women's acceptance of HIV/AIDS status. Method: The research is mixed-method with a sequential exploratory. Informants are companion’s HIV/AIDS in Bandar Lampung City. The qualitative phase of data collection with in-depth interviews with nine informants from 3 HIV/AIDS communities/networks was selected by purposive sampling. The quantitative phase used an online questionnaire to women living with HIV/AIDS who live in Bandar Lampung City and are a support group from 3 HIV/AIDS communities/networks, obtaining 27 people during two weeks of data collection. Qualitative analysis with content analysis and quantitative analysis with univariate analysis. This research was conducted for eight months (January – September 2021). Results: The results of the study where the success of acceptance of HIV/AIDS status in women in the excellent category was 25 (92.6%) where the companion used an empowerment strategy through the stages of collaboration, case finding, self-introduction, exploring problems, and self-potential, implementation of accompaniment and monitoring and evaluation by utilizing the media whats app group and methods of personal approach and peer support groups. Suggestions, so that the length of time for acceptance of HIV/AIDS status is faster, the companion needs to get self-acceptance therapy training for women living with HIV/AIDS to empower women.